The largest entry in the inverse of a Vandermonde matrix. Issue 20 (19th December 2022) - Sanna, Carlo; Shallit, Jeffrey; Zhang, Shun
Abstract : We investigate the size of the largest entry (in absolute value) in the inverse of certain Vandermonde matrices. More precisely, for every real b > 1, let M b ( n ) be the maximum of the absolute values of the entries of the inverse of the n × n matrix [ b i j ] 0 ≤ i, j < n . We prove that lim n → + ∞ M b ( n ) exists, and we provide some formulas for it.